الابداع والابتكار المقاولاتي لدى طلبة معاهد علوم وتقنيات النشاطات البدنية والرياضية في الجزائر - كسيلي, جمال; ناصري, محمد الشريف; تيايبية, فوزي (تيايبية,فوزي. كسيلي,جمال. ناصري,محمد الشريف. الابداع والابتكار المقاولاتي لدى طلبة معاهد علوم وتقنيات النشاطات البدنية والرياضية في الجزائر. مجلة السراج في التربية وقضايا المجتمع. مج 07ع04. 30/12/2023. جامعة الوادي [أكتب تاريخ الاطلاع] متاح على الرابط[أنسخ رابط التحميل], 2023)
هدفت هاته الدراسة الى التعرف على الفروق بين طلبة علوم وتقنيات النشاطات البدنية والرياضية في بعد الابداع والابتكار تبعا لمتغير مكان السكن والجنس وفق اختبار مان ويتني. وذلك باستخدام استبيان الفكر المقاولاتي المعد وفق عدة أبعاد من بينها بعد الابداع والابتكار في دراستنا، وتمثل مجتمع دراستنا في طلبة معاهد علوم و تقنيات النشاطات البدنية و الرياضية بحيث اختيرت العينة بالطريقة العشوائية الطبقية، وذلك وفق المنهج الوصفي في شكله المسحي. وتوصلت الدراسة الى انه لا توجد فروق ذات دلالة احصائية بين طلبة معاهد علوم وتقنيات النشاطات البدنية والرياضية في الابداع والابتكار المقاولاتي تبعا لمتغير مكان السكن وتبعا لمتغير الجنس.Abstract : This study aimed to identify the differences between students of science and technology of physical and sports activities in the dimension of creativity and innovation according to the variable of place of residence and gender according to the Mann-Whitney test. And by using a questionnaire of entrepreneurial thought prepared according to several dimensions, including the dimension of creativity and innovation in our study, The population of our study consisted of students from the institutes of science and technology of physical and sports activities, so the sample was chosen by the stratified random method, according to the descriptive method in its survey form. The study found that there are no statistically significant differences between the students of the institutes of science and technology of physical and sports activities in creativity and entrepreneurial innovation, according to the variable of place of residence and according to the gender variable.
مقال
Keywords: ابداع ؛ ابتكار ؛ مقاولتية; creativity ; innovation ; Entrepreneurship